Preferences of Traditional Market Traders in Deciding to Use Quick Response Code Indonesia Standard (QRIS) as a Transaction Tool - Musriani , M.; Sanaba, Hardiman F. (Jurnal Manajemen Bisnis, 2024)
The preference of traditional market traders in using QRIS as a non-cash payment transaction method in the traditional market of sorong district is considered ineffective because the perception of traders towards the use of QRIS has a negative perception. The results of the study indicate that the Qris payment system is not ready to be used in traditional markets, especially the Traditional market of Sorong Regency. The four main factors that the payment system has not been continuity in its use are the perception of strongly disagreeing with QRIS providing benefits from other payment systems, as well as the perception of disagreeing with QRIS can increase sales, QRIS can increase the number of consumers, and the use of QRIS as a transaction tool that can protect personal data and transaction data when transacting, QRIS as a transaction tool that can guarantee access and data both personally and payment transactions. However, traditional market traders in Sorong Regency have a positive perception of QRIS as a transaction tool to speed up payment transactions, therefore the need for socialization to the public of the benefits of using QRIS as a transaction tool.